The relationship between organizational structure and organizational ambidexterity : A comparison between manufacturing and service firms - Kortmann, Sebastian (Betriebswirtschaftliche Studien in forschungsintensiven Industrien, 2012)
Sustainable competitive advantage is dependent on a firm's ability to simultaneously balance different activities in a trade-off situation. This capability is referred to as organizational ambidexterity and may comprise various paradoxical activities, such as exploration and exploitation. To enhance the current understanding of organizational ambidexterity and how it can be realized, Sebastian Kortmann provides at least three important contributions. Apart from the development of a theoretical framework for ambidexterity, the study uncovers which structural mechanisms support ambidextrous behavior and the extent to which these relationships are dependent on firm type.